Microcredential for Physics Majors - López, Jorge A.; Muñoz, Jorge A. (Cultura Científica y Tecnológica, 2024)
This article describes the benefits of using microcertifications to complement undergraduate physics courses. A microcertification program developed for the physics undergraduate program at University of Texas at El Paso is described, including modules created by the Data Science Community of Practice (DSCOP) group, part of the American Physical Society Data Science Group, on topics of data science, machine learning and artificial intelligence applied to physics topics.